2020
DOI: 10.1101/2020.03.18.997833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scleraxis is required for the growth of adult tendons in response to mechanical loading

Abstract: Scleraxis is a basic helix-loop-helix transcription factor that plays a central role in promoting tenocyte proliferation and matrix synthesis during embryonic tendon development.However, the role of scleraxis in the growth and adaptation of adult tendons is not known. We hypothesized that scleraxis is required for tendon growth in response to mechanical loading, and that scleraxis promotes the specification of progenitor cells into tenocytes. We conditionally deleted scleraxis in adult mice using a tamoxifen-i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Proteins of interest for immunolabelling were selected based on their expression by tendon progenitor cell subpopulations in previous reports (Yin et al, 2016) and their predicted interactions in Equus caballus (NCBI taxid: 9796) using STRING (version 10.5) networkbased predictions for CD146 and LAMA4 (Szklarczyk et al, 2017;Gumucio et al, 2020).…”
Section: Network-based Predictions Of Cd146 Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins of interest for immunolabelling were selected based on their expression by tendon progenitor cell subpopulations in previous reports (Yin et al, 2016) and their predicted interactions in Equus caballus (NCBI taxid: 9796) using STRING (version 10.5) networkbased predictions for CD146 and LAMA4 (Szklarczyk et al, 2017;Gumucio et al, 2020).…”
Section: Network-based Predictions Of Cd146 Interactionsmentioning
confidence: 99%
“…In adult tissues, cell surface markers, such as CD44 and CD90 (THY1), are members of a number of canonical marker panels routinely used in the characterisation and isolation of specific stromal/stem cell populations (Horwitz et al, 2005;Morath et al, 2016). Recent studies have also reported resident CD146 populations in tendon (Yin et al, 2016;Gumucio et al, 2020). CD146 or melanoma adhesion molecule (MCAM; MUC18; Gicerin; OMIM:155735) is a transmembrane glycoprotein belonging to the IgG superfamily of cell adhesion molecules (Shih, 1999).…”
Section: Introductionmentioning
confidence: 99%